Effect of Gestational Biological, Social, Economic Factors on Undernutrition in Infants 6-12 Months in Cilacap - Septikasari, Majestika; Akhyar, Muhammad; Wiboworini, Budiyanti (Indonesian Journal of Medicine, 2016)
Background: Undernutrition in children under five can cause disorder in the physical growth, mental development, low intellegence, or even death. This study aimed to test the hypothesis that under nutrition in infants aged 6-12 months is associated with gestational biological, social, and economic factors.Subjects and Method: This was an analytic and observational study with case control design. This study was conducted in Cilacap, Central Java. A total of 144 infants aged 6-12 months were selected by fixed disease sampling, consisting of 72 undernutrition cases and 72 control. The dependent variable was undernutrition. The independent variables were birthweight, breastfeeding complementary food intake, exclusive breastfeeding, maternal education, paternal education, family income, MUAC at pregnancy, intra-household food allocation, and rural-urban residence. The data were collected by questionnaire and anthropometry. The data were analyzed by multiple logistic regression.Results: Birthweight <2500 gram (OR=8.12; 95% CI=0.92 to 71.64; p=0.059), inadequate intake of breastfeeding complementary food (OR=3.93; 95% CI=1.59 to 9.75; p=0.003), and non-exclusive breastfeeding (OR=2.46; 95% CI=1.13 to 5.36; ÃÂ p=0.023) increased the risk of undernutrition in infants aged 6-12 months. Paternal education (OR=1.50; 95% CI=0.61 to 3.71; p=0.377), family income (OR=2.54; 95% CI= 1.03 to 6.28; p=0.43), MUAC (OR=1.32; 95% CI=0.512 to 3.38; p=0.562), intra-household food allocation (OR=1.84; 95% CI=0.85 to 4.02; p=0.123), maternal education (OR=0.78; 95% CI=0.31 to 1.97; p=0.599) and rural-urban residence (OR=0.82; 95% CI= 0.36 to 1.85; p=0.630) had non-significant effect on the risk of undernutrition in infants aged 6-12 months.Conclusion: Birthweight <2500 gram, inadequate intake of breastfeeding complementary food, and non-exclusive breastfeeding increase the risk of undernutrition in infants aged 6-12 months. Paternal education, family income, MUAC, intra-household food allocation, maternal education and rural-urban residence have non-significant effect on the risk of undernutrition in infants aged 6-12 months.Keywords: birthweight, gestational, biological, social, economic factors, undernutrition, infants aged 6-12 monthsCorrespondence:ÃÂ Majestika Septikasari. School of Health Al-Irsyad Al-Islamiyyah Cilacap, Central Java. Email: jeaflava@gmail.comIndonesian Journal of Medicine (2016), 1(3): 184-194https://doi.org/10.26911/theijmed.2017.02.01.06